(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Immobilization hypercalcemia is a diagnosis in which excessive bone metabolism abnormalities andconditions related to reduced movement such as medullar lesions or vascular cases. Investigation needs amore evaluation to find out other causes of hypercalcemia.Incidence rate of immobilization hypercalcemiais 11?22% in spinal cord injury group and 20?30% in immobilized patients secondaryto fractures in 2 caseseries .Usually itoccurs 4?6 weeks post trauma (1 week?16weeks)may stay elevated for up to 12 monthsbased onmobilization. Aim-To determine the prevalence of hypercalcemia among immobilized patients.Materials and Methods-An analytical research approach and a cross-sectional research design were used.The study was conducted in Acharya Vinoba Bhave Rural Hospital; Sawangi Meghe Wardha.The sampleswere selected using purposive sampling technique, sample size was 30 and blood test done for screeningafter written informed consent.There were total 30 patients, blood samples which were carried out duringstudyperiod, it was concluded that out of 30 immobilized patients 14 patients is having hypercalcemia inimmobilized state. The study found that there was a person suffering from hypercalcemia in their immobilizedstate. Hence this study helps in treatment of hypercalcemia during their immobilized state of the patients.From this study it is concluded that 46.67 % of the patients suffering from hypercalcemia.